Understanding and Prevention of “Therapy-” Induced Dyskinesias - Iciar Aviles-Olmos; Zinovia Kefalopoulou; Thomas Foltynie (Parkinson's Disease)
L-dopa is the most effective, currently available treatment for Parkinson’s disease (PD), but it leads to the development of involuntary movements known as L-dopa-induced dyskinesia (LID) in the majority of patients after long-term use. Both gene and cell therapy approaches are the subject of multiple ongoing studies as potential ways of relieving symptoms of PD without the complication of dyskinesia. However, the spectre of dyskinesia in the absence of L-dopa, the so-called “off-phase” or graft-induced dyskinesia (GID), remains a major obstacle particularly in the further development of cell therapy in PD, but it is also a concern for proponents of gene therapy approaches. LID results from nonphysiological dopamine release, supersensitivity of dopamine receptors, and consequent abnormal signalling through mechanisms of synaptic plasticity. Restoration of physiological circuitry within the basal ganglia loops is ultimately the aim of all cell and gene therapy approaches but each using distinctive strategies and accompanied by risks of exacerbation of LID or development of “off-phase”/GID. In this paper we discuss the details of what is understood regarding the development of dyskinesias with relevance to cell and gene therapy and potential strategies to minimize their occurrence.